Isolate Gram Negative Bacteria Resistant Antibiotics Carbapenems in Maternal Urine Pregnant - Mahmud, Abbas; Haninggar, Rizki Dyah; Akbar, Fajar (Poltekkes Kemenkes Mataram, 2024)
Pregnant women with bacterial uria, more than half have infections with antibiotic- resistant organisms. This pattern of resistance has a real clinical impact because pregnant women with antibiotic-resistant Gram Negative lower urinary tract infections are estimated to be 2-3 times more likely to develop pyelonephritis. Antibiotic resistance is common among pathogenic bacteria that cause urinary tract infections. Enterobacterales are frequently encountered pathogens that cause community-associated infections, such as urinary tract infections. Urinary tract pathogenic bacteria are generally caused by Escherichia coli, Staphylococcus aureus Klebsiella sp, Escherichia coli is a common cause of bacteriuria symptomatic and asymptomatic. In the era of multidrug resistance, appropriate diagnosis and treatment must be given to avoid in pregnant women and prevent antibiotic resistance. Antibiotic-resistant bacteria pose a serious threat to the mother and fetus because it is difficult to obtain safe antibiotics. Increased bacterial resistance of urinary tract pathogens may complicate the selection of appropriate drugs. This study aimed to determine the sensitivity of carbapenem antibiotics to bacterial isolates from the urine of pregnant women. This type of research is descriptive observational research, where the sample used is urine Pregnant. A urine specimen sample is inoculated to in Brain Heart Infusion Broth (BHIB) media, next inoculated to MacConkey agar medium. Isolate bacteria from MacConkey To be done Gram examination and sensitivity test. Sensitivity test use method diffusion the Kirby-Bauer disc uses an antibiotic disc group Carbapenems namely Meropenem (MER) 10ug. Data in the form of mark sensitivity form resistant (R), Intermediate (I) and Sensitive (S) of antibiotic group, participant data processed use SPSS application. This study obtained there were 5 ( 20 %) Gram Negative bacteria that resistant antibiotic meropenem (MER) from group Carbapenems . Conclusion: There is isolate Gram Negative bacteria from urine pregnancy that resistant to antibiotics meropenem from group carbapenemia. Type of group carbapenems the is the antibiotic